2021
DOI: 10.21037/jgo-20-534
|View full text |Cite
|
Sign up to set email alerts
|

High expression of aldolase A is associated with tumor progression and poor prognosis in hepatocellular carcinoma

Abstract: Background: Aldolase A (ALDOA), a key glycolytic enzyme, has been reported to play an important role in lung, pancreatic, and colorectal cancer. However, the role and mechanism of ALDOA in hepatocellular carcinoma (HCC) are still unclear. This study aimed to study the role and potential mechanism of ALDOA in HCC. Methods: The changes in expression level and clinical implications of ALDOA in HCC were studied through bioinformatics and online databases. The prognostic role of ALDOA was investigated by Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Additionally, high FBP1 correlates with lung squamous cell carcinoma, and low FBP1 correlates with uterine corpus endometrial cancer (p=0.00052). Similar trends were observed in LUAD and LIHC with respect to ALDOA expression and overall survival, first progression, and postp-rogression survival ( Supplementary Figures 2 , 3 ), which is consistent with overexpression of ALDOA being associated with poor prognosis in surgical specimens [ 7 , 15 , 17 , 43 ]. We previously observed that ALDOA expression correlated more strongly with poor prognosis in lung cancer [ 9 , 10 , 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, high FBP1 correlates with lung squamous cell carcinoma, and low FBP1 correlates with uterine corpus endometrial cancer (p=0.00052). Similar trends were observed in LUAD and LIHC with respect to ALDOA expression and overall survival, first progression, and postp-rogression survival ( Supplementary Figures 2 , 3 ), which is consistent with overexpression of ALDOA being associated with poor prognosis in surgical specimens [ 7 , 15 , 17 , 43 ]. We previously observed that ALDOA expression correlated more strongly with poor prognosis in lung cancer [ 9 , 10 , 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, the proteomic analysis revealed differential expression of glycolysis pathway, being lactate dehydrogenase A (LDHA), lactate dehydrogenase B (LDHB) and fructose-biphosphate aldolase A (ALDOA), the identified downregulated glycolytic enzymes by ( IA ) treatment. ALDOA is a key glycolytic enzyme, the high expression of which has been associated to tumor progression and poor prognosis in hepatocellular carcinoma [ 33 ]. Glycolytic enzymes play a physiological role that is not limited to catalytic function and can participate as regulators of cellular processes, such as actin filaments organization, p53 signaling, and cell cycle progression, considered as necessary cellular events for survival and proliferation of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In order to visualize the different clusters involved in pro-apoptotic activity of IA , we performed a Protein–Protein Interaction Analysis (PPI) of differentially expressed proteins ( Figure 5 ) and the results obtained suggest that the possible action mechanism may be the apoptosis activation, where glycolytic enzymes ALDOA, LDHA and LDHB were biologically connected to pro-apoptotic proteins as BAX and BID, as well to the glutathione transferases MGST1 and GSTK1 [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies about the dysregulation of the ALDOA gene have emerged in recent years, including colorectal cancer (Dai et al, 2018), gastric cancer (Jiang et al, 2018), and renal cell carcinoma (Huang et al, 2018). Previous bioinformatics results also indicated that ALDOA expression was correlated with prognosis in bladder cancer (Li et al, 2019), hepatocellular cancer (Tang et al, 2021). In lung cancer, overexpression of ALDOA is reported to promote lung cancer cell proliferation and metastasis (Chang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, ROC curve analysis suggested that ALDOA can act as a prospective non-invasive diagnostic biomarker to differentiate lung adenocarcinoma tissues from adjacent normal tissues. Previous studies reported that upregulation of ALDOA is correlated with poor prognosis in colorectal cancer ( Dai et al, 2018 ), gastric cancer ( Jiang et al, 2018 ), and hepatocellular carcinoma ( Tang et al, 2021 ). Our data on survival analysis with GEPIA2 and the Kaplan Meier plotter indicated that lung adenocarcinoma patients with high ALDOA expression or genetic alteration have a poor overall survival prognosis.…”
Section: Discussionmentioning
confidence: 99%